Ship Production Cost Analysis of Conversion From Minajaya 11 Tuna Long Liner Ship to Fish Carrier Ship - Taufik Fajar Nugroho; Raja Oloan Saut Gurning; Eddy Setyo Koenhardono; Irfan Byna Nur Akbar (Institut Teknologi Sepuluh Nopember, 2019)
MV Minajaya Tuna Long Liner Ship number 11 is a fishing vessel and one from 24 Minajaya shipsets owned by PT. Industri Kapal Indonesia (IKI). Minajaya 11 has 512 GT capacity hence, it is prohibited by the government to be operated. Therefore Minajaya 11 will be converted into fish carrier vessel, fish carrier vessel scenario itself is sailing to several fishing grounds locate at WPP 716 in Indonesia and to objectify Minajaya 11 as fish carrier vessel, ship production cost has to be analyzed. The Calculation of ship production cost generally divided into three different types, those are reparation, installation and dismantling, from three different groups there are divided into 4 different task, human resources, material, equipment and energy cost. The total cost from reparation is Rp. 850.000.000 with the biggest proportion came from human resources with 49% proportion and the lowest proportion came from energy price with 2% proportion. The total cost from installation is Rp. 1.545.000.000 with the biggest proportion came from material and shipping cost with 88% proportion and the lowest proportion came from energy cost with 0% proportion. The total cost from dismantling is Rp. 25.700.000 with the biggest proportion came from human resources cost with 77 % proportion and the lowest proportion came from material cost with 0% proportion. Total conversion production cost needed by Minajaya 11 is Rp. 2.902.000.000 while the conversion activities will be finished in 5 months and 6 days approximately.